Engaging Mothers and Community Health Workers: An Online Maternal and Children’s Health Education in Kampung Lio, Indonesia - Aurelia, Shafira; Andini, Dheanita Nissrina; Soloan, Garry; Waladhiyaputri, Vahira; Friska, Dewi (UI Scholars Hub, 2023)
To raise awareness and understanding of maternal and children’s health, a team from Faculty of Medicine, Universitas Indonesia, Indonesia, conducted a program called Tinggi Cerdas. It is a community development program in Kampung Lio, Depok, West Java. This article evaluates the impacts of activity related to the participant’s awareness and knowledge about maternal and children’s health. The program was developed and conducted as an online program due to the COVID-19 pandemic situation, from September to December 2021. The program was developed with four different topics through online communication, equipped with an educational booklet for the mothers and a PrimaKu® application for health workers. Such approaches were employed to provide the community with better health awareness and understanding, as well as an instrument for the health workers to monitor the condition of the participants. Community health workers (CHWs) were given a workshop about the application to help them in raising mothers’ awareness to monitor their children’s growth and development. To examine the impacts of the program, pre- and post-tests were used to evaluate the impact on the participants’ knowledge—the mothers’ and CHWs’. The result of the program’s assessment suggests that mothers’ knowledge and awareness about children’s and maternal health are improved, particularly when the application was also utilized by the CHWs in Kampung Lio. The participants are satisfied with the program, implying the program should be repeated. Despite the limitations, health education for mothers and CHWs could be carried out successfully. Insights and reflections are provided in this study to encourage readers to develop a more effective program in the future.